The Relationship between Pregnant Women's Knowledge about Anemia and Compliance with the Consumption of Iron Supplements - Fitria Anggraeni; Endah Mulyani; Amalia Rahma; Dwi Novri Supriatiningrum; ⁠Eka Sri Rahayu Ariestiningsih (Indonesian Journal of Global Health Research, 2025)
In pregnant women, iron consumption is used as an effort to overcome iron deficiency. Where the coverage of pregnant women will get a minimum of 90 tablets of Fe tablets during pregnancy because at that time the need for iron is very high. Pregnant women who do not understand the importance of the level of knowledge with adherence to consuming Fe tablets which will have an impact on the mother and also the fetus. This study was conducted to determine the relationship between knowledge of pregnant women and adherence to consuming Fe tablets at the Lamongan Public Health Center. This research is a descriptive observational study with a cross sectional design. The population in this study were pregnant women, totaling 719 samples taken using purposive sampling where the number of samples was taken in consideration. The data obtained is by distributing questionnaires that have been validated and tested for reliability by previous researchers, then the questionnaires are filled in directly by the respondents. Data analysis was carried out in the form of unvariate analysis and bivariate analysis using the chi-square test. The results showed that the knowledge of pregnant women about iron was in the good category (83,7%), and the adherence of pregnant women to consume Fe tablets was in the obedient category (17,3%). While the knowledge of pregnant women in the poor category (81,5%), and the compliance of pregnant women in the non-compliant category (18,5%). The conclusion in this study was that there was a significant relationship between knowledge of pregnant women and adherence to consuming Fe tablets at the Lamongan Health Center with p = 0.001.